PENILAIAN RISIKO PEKERJAAN SERVIS UNIT RODA DUA PADA PT. ASTRA INTERNATIONAL DI BALIKPAPAN - Ananta , Erwin; Liku, James. E.A; Mappangile , Andi Surraya; Najamuddin, Najamuddin (Program Studi Kesehatan dan Keselamatan Kerja, 2023)
Occupational Health and Safety (K3) is an activity that ensures the creation of safe working conditions, protected from physical and mental disorders through coaching and training, directing, and controlling the implementation of tasks from employees and providing assistance in accordance with applicable regulations, both from institutions government and the companies they work for. PT. Astra International Tbk-Honda in terms of Occupational Safety and Health has not carried out a risk assessment of service activities in its workshop, therefore it is necessary to identify hazards and risk assessments as well as control the service work of the two-wheeled unit. The research method used by the author is a qualitative descriptive methodology. With data collection techniques, namely interviews, observations and documentation. After the researchers conducted research with observations and interviews, the data obtained, compiled, grouped and then interpreted objectively so that an overview of the problems studied was obtained. Two are activities that have a high risk and from the Two Wheel Unit Service activity there are 19 risks from 3 stages of tube heat exchanger maintenance activities. The risk assessment was carried out on 19 emerging risks, after the assessment, it was found that from 19 emerging risks there were 9 risks with a high risk level, 8 risks with a medium risk level, and 2 risks with a low risk level. Risk control is carried out using a hierarchy of control guidelines (elimination, substitution, technical control, administration, and personal protective equipment), the results of the assessment of 19 risks have decreased to 19 risks with 6 levels of medium risk and 13 levels of low risk.